Development of ‘proplant’ gamification model for plant reproduction subtopic in form 1 science subject - Nor, N. A. M.; Wahid, N. B. A. (AIP conference proceedings, 2023)
This study aims to develop a gamification model, ‘ProPlant’ for the subtopic of Plant Reproduction, in Form 1, Science subject. In addition, the level of usability of the ‘ProPlant’ game from the perspective of trainee teachers were also determined. The research design is the developmental research based on ADDIE model. The data were analyzed quantitatively through questionnaires. A total of 20 trainee teachers from the Bachelor of Education (Biology) program, Universiti Pendidikan Sultan Idris were involved in the pilot study, while 51 trainee teachers were selected as the actual sample (based on convenience sampling). The data obtained were analyzed using the Statistical Package for Social Science (SPSS). The reliability coefficient of the questionnaire (Cronbach’s Alpha) obtained from the pilot study is 0.934 which is classified as very good. The results showed that the value of face and content validity of the gamification and the questionnaire are 92.1% expert agreement. The overall mean value for the suitability of the ‘ProPlant’ Gamification Model is 3.86 and for the use of the ‘ProPlant’ Gamification Model in learning and facilitation is 3.87. This result indicates that the level of usability of the ‘ProPlant’ game is high. In conclusion, this model is very suitable for the use by teachers in learning and facilitation to create an interactive learning environment while making learning session more fun with the use of gamification. With the presence of the ‘ProPlant’, it is hoped that students will be able to master the subtopic of Plant Reproduction in the Form 1 Science subject.